2019
DOI: 10.1093/hropen/hoz006
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of ICSI versus conventional IVF in couples with non-male factor infertility: study protocol for a randomised controlled trial

Abstract: Study questions Does ICSI result in a higher live birth rate as compared with conventional IVF in couples with non-male factor infertility? What is known already ICSI is primarily indicated for severe male factor infertility. While the use of ICSI for couples with non-male factor infertility has been increasing worldwide, this is not supported by data from randomised controlled trials. Evidence from non-randomised studies suggest no benefit from ICSI compared with conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Contrary to these reports, Moghadam et al [ 143 ] reported that motility did not enhance fertilization rate or improve pregnancy outcome through IVF. Further, with the advent of ICSI, the use of conventional IVF practice has drastically reduced [ 144 ].…”
Section: Importance Of Motility In Planning Therapeutic Insemination mentioning
confidence: 99%
“…Contrary to these reports, Moghadam et al [ 143 ] reported that motility did not enhance fertilization rate or improve pregnancy outcome through IVF. Further, with the advent of ICSI, the use of conventional IVF practice has drastically reduced [ 144 ].…”
Section: Importance Of Motility In Planning Therapeutic Insemination mentioning
confidence: 99%
“…However, the probability of IVF fertilization success seems to be independent of the percentage of normal forms, excluding its role as a reliable prognostic marker 12 . Since the advent of the intracytoplasmic sperm injection (ICSI), the use of conventional IVF progressively decreased 13 . Despite the direct microinjection of a single spermatozoon into the oocyte, the use of non‐motile spermatozoa seemed to negatively impact fertilization outcome 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 12 Since the advent of the intracytoplasmic sperm injection (ICSI), the use of conventional IVF progressively decreased. 13 Despite the direct microinjection of a single spermatozoon into the oocyte, the use of non‐motile spermatozoa seemed to negatively impact fertilization outcome. 5 In addition, similarly to IVF, the prognostic value of sperm morphology remains poor also in the ICSI context.…”
Section: Introductionmentioning
confidence: 99%
“…An ongoing RCT is being performed to compare the efficacy of ICSI and IVF. Its primary endpoint is live birth of the first embryo transfer after IVF/ICSI, including both fresh and frozen transfer ( 37 ). Secondly, our previous study showed the endometrial preparation protocol of AC had a higher LBR, compared with NC protocol ( 38 ).…”
Section: Discussionmentioning
confidence: 99%